¬Pengaruh Transparansi, Akuntabilitas dan Kualitas Pengelolaan Zakat, Infaq dan Shadaqoh terhadap Minat Masyarakat Berdonasi di Lembaga Amil Zakat Al-Washliyah - Khoirunnisa Ritonga; Tuti Anggraini; Arnida Wahyuni Lubis (Universitas 45 Surabaya, 2024)
This research aims to find out the influence of transparency, accountability and quality of management of zakat, infaq and shadaqoh on people's interest in donating at the Amil Zakat Al-Washliyah Institute. This research uses a quantitative approach, the population in this study is all including muzaki, infaq and shadaqah donors. totaling 300 people, the sample used used the Slovin method with a total of 75 respondents, the data analysis technique used in this research was multiple linear regression analysis, the results of this research were, Transparency influences people's interest in donating, seen from the calculated t value > t table (2.076> 1.993) and sig value 0.041 < 0.05, Accountability has no influence on Community Interest in Donating, seen from the calculated t value > t table (1.759 < 1.993) and sig 0.083 > 0.05, Management Quality has no influence on Community Interest in Donating , from the results of the table above, the calculated t value is greater than the t table in this case (1,499 < 1,993) and the sig value is 0.138 < 0.05. Simultaneously Transparency, Accountability and Quality of Management influence the Public's Interest in Donating to the Al-Washliyah Amil Zakat Institution in this case f count > ftable (29.029 > 3.12) and significant level (0.000 < 0.05), the R Square value of 0.551 means 55.1% of the bond size of the variable Transparency, Accountability and Quality of Management towards Community Interest Donating to Al-Washliyah Amil Zakat Institution , while the remaining 44.9% was influenced by other factors not studied.